ANALISIS PAJAK DAERAH DAN RETRIBUSI DAERAH DALAM STRUKTUR PENDAPATAN ASLI DAERAH KOTA MANADO - Suratinoyo, Ali Kurniawan A.; Sabijono, Harijanto; Alexander, Stanly (Universitas Sam Ratulangi, 2013)
Local Revenue constitutes acceptance of levy local taxes, retribution, separated management of regional assets and other income. The higher income of regional income was an image of success level ability in financing administering government and regional development. Local taxes and retribution is a major source of Acceptance for local revenue used to finance governance and development. Purpose of the implementation of this study to determine the growth of local taxes and retribution in the revenue structure of Manado. The processed data is the data from the Office of Manado City revenues from 2007 to 2011. Data analysis method used is descriptive method to analyze the data of actual local taxes and retribution years 2007-2011 were obtained from the Regional Revenue Office of Manado City. Results of this study indicate that the contribution of a given local taxes and retribution Â to revenue from 2007 to 2011 in the amount of 65.18% to 23.16% and local taxes for retribution. The lack of total revenues compared to retribution local taxes, the local government should further optimize Manado services rendered, whether commercial in nature or in the form of public service.